Unique cessation tools in the box: Quitline utilization and effectiveness trends among a large sample of tobacco users reporting mental health disorders - Hart, Jonathan T.; Boeckman, Lindsay M.; Beebe, Laura A. (Frontiers in Psychiatry, 2022)
It is estimated that the prevalence of smoking among adults with MHDs ranges between 40-60%, as compared to about 17% among those without an MHD. In addition, smokers with MHDs smoke more cigarettes, are more nicotine dependent, and experience more difficulty quitting, compared to other smokers. The US Public Health Service guidelines, as well as the National Cancer Institute, strongly recommend quitlines as an evidence-based treatment strategy to reduce barriers to cessation treatment, especially among smokers with MHDs; however, the literature is sparse on quitline engagement trends and associated outcomes for quitline participants with MHDs. This study sought to contribute to this gap with the largest sample to-date of MHD-endorsing tobacco quitline (Oklahoma Tobacco Helpline, OTH) participants. From 2015-2020, approximately 65,000 registrants identified as having one or more MHDs in addition to their tobacco use. This study tested for the presence of significant differences between groups with and without MHDs (as well as within the MHD-identified group) on program selections, engagement intensity with chosen services, NRT utilization, and quit rates. It also tested for differences and moderating effects of demographic variables associated with the comparison groups. Statistically significant differences were found between these two groups with regard to: sex, age, racial identity, education level, annual income and insurance status. Significant differences were also found with tobacco use patterns (e.g., reported timing and daily use amounts). Differences in quitline program selection were demonstrated, such that the MHD-endorsing sample were more likely to participate and agree to the most robust service available. Significantly higher rates of service intensity (number of services engaged) were demonstrated, and MHD individuals were also significantly more likely to receive NRT as a part of their treatment. This study suggests a simplistic “more is better” quitline services approach may suffer in effectiveness because it neglects barriers common to this population. Important information is provided on these unique variables associated with MHD-endorsing individuals trying to quit their tobacco use. These results can help tobacco quitlines conceptualize the unique difficulties experienced by individuals with MHDs and then tailor their approach to respond supportively and constructively to this high need group.